2023
DOI: 10.1051/cagri/2023007
|View full text |Cite
|
Sign up to set email alerts
|

Contribution des résidus de culture à la réduction du déficit alimentaire des troupeaux de ruminants dans l’Ouémé Supérieur au Bénin

Abstract: L’utilisation de la biomasse des résidus de cultures présents sur les exploitations agricoles après les récoltes est importante pour alimenter les animaux durant la saison sèche. La présente étude vise d’une part à estimer la biomasse des résidus au champ, et d’autre part à analyser la capacité de charge qui en résulte dans l’Ouémé Supérieur au Bénin. Des enquêtes ont été réalisées auprès d’agriculteurs et d’éleveurs, ainsi que des mesures de biomasses de résidus. Trois cents éleveurs ont été interrogés sur l’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…However, these residues were used the most in animal feed during the dry season. These results are similar to those obtained by other authors [ 53 , 54 ], who showed that crop residues are much more used in livestock feed in dry periods. While herbaceous fodder is abundant during the rainy season and can cover all the feed needs of the herds, in the dry season, herbaceous fodder becomes scarce [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, these residues were used the most in animal feed during the dry season. These results are similar to those obtained by other authors [ 53 , 54 ], who showed that crop residues are much more used in livestock feed in dry periods. While herbaceous fodder is abundant during the rainy season and can cover all the feed needs of the herds, in the dry season, herbaceous fodder becomes scarce [ 55 ].…”
Section: Discussionsupporting
confidence: 92%